Plant-Based Feed and Vitamin E Enhance Reproductive Maturation in Female Cherax quadricarinatus - Iskandar, Andri; Ansarullah, Habib; Lesmanawati, Wida; Hendriana, Andri (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2025)
The freshwater lobster Cherax quadricarinatus is an aquaculture commodity with high economic value, yet it remains relatively unfamiliar to the general public. Nevertheless, market demand for this species has shown a significant upward trend, both domestically and internationally. In Indonesia, the increase of aquaculture production specially on freshwater lobster has not been sufficient to meet existing demand, primarily due to the limited availability of high-quality broodstock and the low reproductive capacity of female brood lobsters. One potential strategy to address this issue is the optimization of feed quality. This study aims to evaluate the effects of a dietary combination consisting of mung bean sprouts (Vigna radiata), white sweet potatoes (Ipomoea batatas), and commercial pellets enriched with vitamin E on the reproductive performance of female freshwater lobsters. The results indicated that the best feed formulation was observed in Treatment P3, which consisted of 25% mung bean sprouts, 50% Fengli 3 pellets + vitamin E, and 25% white sweet potatoes. This treatment accelerated gonadal maturation to 25 days and resulted in a fecundity of 467.33 eggs, a fertilization rate (FR) of 97.84%, a hatching rate (HR) of 92.70%, and a survival rate (SR) of 90.87%. The content of vitamins A, C, and E in mung bean sprouts is known to stimulate spawning and enhance embryo hatchability, while bioactive compounds in white sweet potatoes contribute to the synthesis of reproductive hormones such as estrogen and vitellogenin.